Navigation and history of science: autopsy to submarine Kursk. Survival previsions were not sufficient - Ignacio Jáuregui-Lobera (Asociación Para el Progreso de la Biomedicina, 2018)
On August 12, 2000, Saturday, a Russian submarine of the Oscar II class, the K-141 Kursk, sank in the Barents Sea, while sailing as part of the "Summer-X Exercise" manoeuvres. The Kursk was a giant double-hulled submarine, with nine sealed compartments, considered impossible to be sunk. During the manoeuvres, at 08:51 local time, the Kursk requested permission to prepare a torpedo and it received the response "Dobro" (good in English). At 11:29:34 (07:29:50 UTC) the Norwegian seismic monitoring network (NORSAR) registered an earthquake of intensity 1.5 on the Richter scale at northeast of Murmansk, approximately 250 Km from Norway, and 80 Km from the Kola Peninsula. At 11:31:48, two minutes and fourteen seconds later, a second movement, 4.2 on the Richter scale and 250 times longer than the first, was recorded by different seismographs, even being detected in Alaska. It was equivalent to an explosion of 2-3 Tm of TNT. After a great confusion and propaganda, there was no choice other than to accept the facts: the Kursk had suffered two explosions, had sunk and the whole crew had perished. But what happened in that submarine? It seems clear that survival previsions were not sufficient.